The Effect of Problem-Based Learning (PBL) on Critical Thinking and Social Science Concept Mastery in SMPN 4 Makassar - Hajriani S; Elpisah Elpisah; Nurdin Nurdin (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the impact of the Project-Based Learning (PBL) model in improving critical thinking skills (Higher Order Thinking Skills/HOTS) and mastery of Social Science (IPS) concepts among 8th-grade students at UPT SPF SMPN 4 Makassar. A quasi-experimental design with a nonequivalent control group was used, involving an experimental group (PBL) and a control group (conventional learning). The sample consisted of two classes (30 students per class) selected purposively. Data were collected through HOTS essay tests (pretest-posttest), PBL-based worksheets, and observation sheets. Data analysis was conducted using parametric statistical tests (independent sample T-test) supported by IBM SPSS Statistics 22 and Cohen’s d for effect size. The results show that, 1) the pretest indicated critical thinking and concept mastery were in the